I've Got My Eyes On You : a Novel - Clark, Mary Higgins (New York : Simon & Schuster, 2018)
"After a party when her parents are away, eighteen-year-old Kerry Dowling is found fully dressed at the bottom of the family pool. The immediate suspect is her boyfriend who had a bitter argument with her at the party. Then there is a twenty-year-old neighbor who was angry because she didn't invite him to the party. Or is there someone else who has not yet been seen on the radar? Kerry's older sister Aline, a twenty-eight-year-old guidance counselor, is determined to assist the Prosecutor's Office in learning the truth"--
Keywords: Drowning victims -- Fiction; People with mental disabilities -- Fiction; Student counselors -- Fiction; Teenage girls -- Fiction -- Crimes against; Murder -- Fiction -- Investigation; FICTION / Suspense; FICTION / Mystery & Detective / General; FICTION / General; New Jersey -- Fiction; Detective and mystery fiction; Thrillers (Fiction)